Analisis Perhitungan Kekuatan Konstruksi Bejana Tekan Menggunakan Nilai Allowable Stress Berdasarkan Pengujian Kekerasan - Risky Utama Putra; Hasan Basri; Dicky Pratama Putra; M Prama Diva Liza; M. Cakra Putra Prakarsa; Akbar Teguh Prakoso (Jurnal Rekayasa Mesin, 2026)
This study aims to analyze the structural strength of a pressure vessel through visual inspection, dimensional measurement, thickness assessment, material hardness testing, and Non-Destructive Testing (NDT) using Magnetic Particle Testing (MT). The methodology included identifying the pressure vessel unit, preparing tools, conducting visual inspections, measuring thickness with an Ultrasonic Thickness Gauge, evaluating hardness with a Leeb Hardness Tester, and performing construction calculations based on ASME Section VIII standards. Results indicated that the actual thickness of the shell (5.0 mm), head (4.0 mm), and tube (3.0 mm) met safety requirements, exceeding the calculated minimum thickness. However, a non-functional pressure gauge was identified, posing a risk to pressure monitoring. NDT MT revealed no defects in welded joints. The study concludes that the vessel is structurally sound but recommends immediate gauge replacement and routine maintenance in compliance with Indonesian Ministerial Regulation No. 37 of 2016 to ensure operational safety.